A digital approach for design and fabrication by rapid prototyping of orthosis for developmental dysplasia of the hip - Munhoz,Rodrigo (2016)
Abstract Introduction Immobilization in a hip spica cast is required in surgical and nonsurgical treatments for children aged three months to four years diagnosed with developmental dysplasia of the hip. Skin complications are associated with the use of the spica cast in 30% of the cases. This research explores the use of photogrammetry and rapid prototyping for the production of a lighter, shower friendly and hygienic hip orthosis that could replace the hip spica cast. Methods Digitalized data of a plastic dool was used for design and fabrication of a customised hip orthosis following four steps: 1) Digitalization of the external anatomical structure by photogrammetry using a smartphone and open source software; 2) Idealization and 3D modeling of the hip orthosis; 3) Rapid prototyping of a low cost orthosis in polymer polylact acid; 4) Evaluation tests. Results Photogrammetry provided a good 3D reconstruction of the dool's hip and legs. The manufacture method to produce the hip orthosis was accurate in fitting the hip orthosis to the contours of the doll. The orthosis could be easily placed on the doll ensuring mechanical strength to immobilize the region of the hip. Conclusion A new approach and the feasibility of both techniques for hip orthosis fabrication were described. It represents an exciting advance for the development of hip orthosis that could be used in orthopedics. To test the effectiveness of this orthosis for developmental dysplasia of the hip treatment in newborns, material and mechanical tests, design optimization and physical tests with patients should be carried.